Rapid Epidemiological Assessment of Onchocerciasis in a Tropical Semi-Urban Community, Enugu State, Nigeria - Je Eyo; Gc Onyishi; Cu Ugokwe (Iranian Journal of Parasitology, 2013)
Background: This study was carried out in Opi-Agu a tropical semi-urban autonomous community comprising of three villages in Enugu State, Nigeria, between the months of April and June 2010. It was designed to determine the prevalence of Onchocerca volvulus infection and assess the perception of the disease among the inhabitants of this community.